Health beliefs on type 2 diabetes: a methodological research for development and psychometric evaluation of "DIABA" (Diabetes-related Instrument to Assess Beliefs of Adolescents) health beliefs on type 2 diabetes - Ameneh Pooresmaeil Dorosteh; Mohtasham Ghaffari; Sakineh Rakhshanderou; Yadollah Mehrabi (BMC, 2023)
Abstract Background Several reports have shown an increase in the number of type-2 diabetics among adolescents creating an extra burden for this age group. However, there is no instrument assessing adolescents' attitude toward this disease. This study aims at designing a psychometric tool for assessing adolescents' health beliefs regarding type-2 diabetes. Research design and methods In this methodological research, 770 boy and girl adolescents (between 13 and 15) from Tehran participated through multistage sampling. The Inclusion criteria were: junior high school students, students' willingness for participation and not suffering from type-1 or type-2 diabetes. The questionnaire was designed by extensive literature review and the related existing questionnaires, as well as considering the research team's comments. The validity of the questionnaire was determined through face and content validity. The construct validity was determined through exploratory and confirmatory factor analysis. Reliability was measured via internal consistency coefficient (ICC) and internal consistency reliability was measured by Cronbach Alpha. SPSS 16 and EQS6.1 were used for data analysis. Results The pool of questions had 57 items, and by removing similar (23 questions) or inappropriate sentences (8 questions), a draft questionnaire with 26 questions was designed. No items were removed in the face validity phase. Based on the results of CVR and CVI, six items and 4 items in the exploratory factor analysis were removed. Finally, a questionnaire with 16 items in 4 dimensions of perceived self-efficacy, behavioral beliefs, perceived susceptibility and perceived severity was obtained. The results of confirmatory factor analysis confirmed the model. The internal consistency coefficient was confirmed measuring Cronbach Alpha at 0.78 and ICC = 0.73. Conclusion The questionnaire designed can be employed as a reliable and valid instrument to assess the psychological perceptions and health beliefs of adolescents with respect to type-2 diabetes.